THE EFFECTIVENESS OF EDUCATION TYPE AND METHOD ON IMPROVING THE ORTHOPEDIC SURGICAL PATIENTS' KNOWLEDGE AND CAPABILITY: A LITERATURE REVIEW: DOI: https://doi.org/10.35654/ijnhs.v2i1.61 - Eni Purwanty (Alta Dharma Publisher, 2019)
Introduction: The success orthopedic surgery patients’ education depends on many factors, including the accuracy in choosing methods and the educational media used. This selection is based on consideration of the appropriateness of the material provided for the patient's needs and the learning objectives to achieve. The purpose of this literature review is to identify the types of methods and educational media employed to improve self-knowledge and abilities of orthopedic surgery patients. Method: The references employed in this literature review were four experimental research articles published in 2010 to2018. The keywords appropriateness in the search were